Standardization and clinical applications of retinal imaging biomarkers for cardiovascular disease: a roadmap from an NHLBI workshop - Chew, Emily Y.; Burns, Stephen A.; Abraham, Alison G.; Bakhoum, Mathieu F.; Beckman, Joshua A.; Chui, Toco Y. P.; Finger, Robert P.; Frangi, Alejandro F.; Gottesman, Rebecca F.; Grant, Maria B.; Hanssen, Henner; Lee, Cecilia S.; et al. (Nature reviews. Cardiology, 2025)
The accessibility of the retina with the use of non-invasive and relatively low-cost ophthalmic imaging techniques and analytics provides a unique opportunity to improve the detection, diagnosis and monitoring of systemic diseases. The National Heart, Lung, and Blood Institute conducted a workshop in October 2022 to examine this concept. On the basis of the discussions at that workshop, this Roadmap describes current knowledge gaps and new research opportunities to evaluate the relationships between the eye (in particular, retinal biomarkers) and the risk of cardiovascular diseases, including coronary artery disease, heart failure, stroke, hypertension and vascular dementia. Identified gaps include the need to simplify and standardize the capture of high-quality images of the eye by non-ophthalmic health workers and to conduct longitudinal studies using multidisciplinary networks of diverse at-risk populations with improved implementation and methods to protect participant and dataset privacy. Other gaps include improving the measurement of structural and functional retinal biomarkers, determining the relationship between microvascular and macrovascular risk factors, improving multimodal imaging ‘pipelines’, and integrating advanced imaging with ‘omics’, lifestyle factors, primary care data and radiological reports, by using artificial intelligence technology to improve the identification of individual-level risk. Future research on retinal microvascular disease and retinal biomarkers might additionally provide insights into the temporal development of microvascular disease across other systemic vascular beds.
Veröffentlicht: 22 July 2024
Gesehen am 18.11.2024